Secondary organic aerosol formation from volatile chemical product emissions: parameters and contributions to anthropogenic aerosol - Sasidharan, Sreejith, author; Jathar, Shantanu, advisor; Volckens, John, committee member; Pierce, Jeffrey, committee member (Colorado State University. Libraries, 2023)
Volatile chemical products (VCP) are an increasingly important source of hydrocarbon and oxygenated volatile organic compound (OVOC) emissions to the atmosphere, and these emissions are likely to play an important role as anthropogenic precursors for secondary organic aerosol (SOA). While the SOA from VCP hydrocarbons is often accounted for in ambient air quality models, the formation, evolution, and properties of SOA from VCP OVOCs remains uncertain. We use environmental chamber data and a kinetic model to develop SOA parameters for ten OVOCs representing glycols, glycol ethers, esters, oxygenated aromatics, and amines. Model simulations suggest that the SOA mass yields for these OVOCs are on the same magnitude as widely studied SOA precursors (e.g., long-chain alkanes, monoterpenes, and single-ring aromatics) and these yields exhibit a linear correlation with the difference between the carbon and oxygen numbers of the precursor. When combined with emissions inventories for two megacities in the United States (US) and a US-wide inventory, we find that VCPs form 0.8-2.5× as much SOA, by mass, as mobile sources. Hydrocarbons (terpenes, branched and cyclic alkanes) and OVOCs (terpenoids, glycols, glycol ethers) make up 60-75% and 25-40% of the SOA arising from VCP use, respectively. This work contributes to the growing body of knowledge focused on studying VCP VOC contributions to urban air pollution.